Microbiological quality of ready- to- eat food sampled from the street vendors of Kubang Kerian, Kelantan - Zin, Sarah Liyana Mohd (Universiti Sains Malaysia, 2015)
Over the years, many food-borne diseases have been reported due to consumption of Ready-To-Eat Food (RTE) that has uncertain microbial quality. The present study was carried out to assess the microbiological quality of various food samples which was vended on streets of Kubang Kerian, Kelantan. A Total of thirty five (n=35) samples were collected from the vendor in an aseptic container and immediately transferred to the laboratory for analysis. The results for microbiological analysis were presented as Total Plate Count (CFU/g), Total Coliform Count (CFU/g), Fecal Coliforms Count or thermotolerant coliforms count (CFU/g), and presence or absence of E.coli. It was found that 74.3% out of 35 samples were unsatisfactory for Total Plate Count and 25.7% of the samples were satisfactory. For Total Coliforms Count, 80% samples were unsatisfactory and 20% of samples were satisfactory. In addition, for Fecal Coliforms Counts, 65.7% samples showed unsatisfactory result and 34.3% samples showed satisfactory result. Six out of 35 samples showed presence of E.coli. This study recommends some preventive measures which the local authorities and food-maker together should follow, and also maintain the standard hygienic procedure to prepare, cook and handle foods. Implementation of such measures, rules and regulations on street food vendors in Kubang Kerian, Kelantan and restaurant are extremely crucial to maintain the hygienic condition as well as to avoid such spreading of harmful organisms through consumption of contaminated foods.